Detrimental effects of adolescent escalating low‐dose Δ9‐tetrahydrocannabinol leads to a specific bio‐behavioural profile in adult male rats. (27th February 2021) - Poulia, Nafsika; Delis, Foteini; Brakatselos, Charalampos; Polissidis, Alexia; Koutmani, Yassemi; Kokras, Nikolaos; Dalla, Christina; Politis, Panagiotis K.; Antoniou, Katerina
Abstract : Background and Purpose: Adolescent cannabis use is associated with adult psychopathology. When Δ 9 ‐tetrahydrocannabinol (THC), mainly in high doses, is administered to adolescence rats there are also long lasting effects in adults. This study aims to determine the specific adult bio‐behavioural profile after adolescent low‐dose THC, which better mirrors adolescent recreational cannabis use. Experimental Approach: Adolescent male Sprague–Dawley rats were treated with escalating low‐dose of THC. In adulthood, they were evaluated for their spontaneous locomotion, sensorimotor gating, higher order and spatial cognitive functions. Dopaminergic activity and cannabinoid receptor expression were measured in distinct brain regions. Hippocampal neurogenic activity of neural stem cells was determined and protein levels of neuroplasticity‐related biomarkers were quantified. Adolescent low‐dose THC exposure increased spontaneous open‐field activity, without affecting prepulse inhibition and attentional set‐shifting performance. Region‐specific dopaminergic alterations and CB1 receptor up‐regulation in the prefrontal cortex were observed. Impaired spatial memory, as assessed with the object location task and Morris water maze test, was associated with significantly decreased proliferative activity (SOX2‐positive cells), neurogenic potential (decreased doublecortin‐positive cells) in the adult hippocampus and defective neuroplasticity, including reduced BDNF expression in the hippocampus and prefrontal cortex. Key Results: Our findings reveal the adverse impact of adolescent low‐dose THC on the psychomotor profile, dopaminergic neurotransmission, compensatory cannabinoid receptor response, cognition‐related neurobiological and behavioural functions. Conclusion and Implications: Our adolescent low‐dose THC animal model does not induce tangible psychotic‐like effects, such as those reported in high‐dose THC studies, but it impairs cognitive functions and points to hippocampal vulnerability and disrupted neurogenesis. Abstract :